Air commando fifty years of the USAF Air Commando and Special Operations Forces, 1944-1994 - Chinnery, Philip D. (Special warfare series, 1994)
Fly anything. Go anywhere. Make the enemy pay. They fly whatever the brass gives them. They land wherever the brass wants them. They have no fear. Slow and low into the teeth of enemy fire, quick and quiet into enemy-held territory, whatever it takes to get the job done, the USAF Air Commandos are the bravest flying men in the world. From the glider pilots who landed deep behind Japanese lines, to the gunship crews who hunted over the dark jungle of the Ho Chi Minh Trail, to Desert Storm's Special Operations choppers...all the daring rescues and last-minute landings are here, straight from the Air Commandos' own stories. Documented with 8 pages of photographs!